Angiotensin-converting Enzyme Inhibitors and Angiotensin Receptor Blockers as Potential Therapeutic Options for Pancreatic Cancer - Asgharzadeh, Fereshteh; Geraylow, Kiarash R.; Khazaei, Majid; Nassiri, Mohammadreza; Hassanian, Seyed Mahdi; Ferns, Gordon A; Avan, Amir (Current Cancer Drug Targets, 2022)
The renin-angiotensin system (RAS) has been reported to have a role in carcinogenesis, and therefore it may be of value as a potential therapeutic target in inhibiting tumor growth. It has been shown that inhibition of RAS via angiotensin I-converting enzyme inhibitors (ACEIs) and angiotensin II type-1 receptor (ARBs) inhibitors may have a protective effect against several malignancies. Here, we provide an overview of the potential value of the RAS pathway and targeting via ACE/ARB inhibitors in pancreatic cancer. Whilst the potential role of RAS as a target for the treatment of pancreatic cancer has been reported, the use of candesartan with gemcitabine failed to improve outcomes in pancreatic cancer. Another study of 1-3 years using ARB was found to reduce the risk of pancreatic cancer. In line with these trials, others have demonstrated that the ARBs in combination with gemcitabine might improve clinical outcomes in patients with advanced pancreatic cancer. Prospective trials are warranted to investigate this hypothesis.
Keywords: carcinogenesis